Lignite-based Organic Fertilizer Improves Soil Quality and Yield of Rice in Belitang South Sumatera - Syafrullah Syafrullah (UNIVERSITY OF LAMPUNG, 2019)
To achieve food-self sufficiency in Indonesia, it is necessary to apply sustainable agriculture practices to improve soil quality. Most of paddy fields have been applied with chemical fertilizers intensively for more than 40 years without the addition of organic matter. The purpose of this study was to understand the effects of lignite-based organic fertilizer application on the quality of paddy soil and yield of rice. The study was conducted in April until August 2014 in the irrigated rice fields in Belitang, Ogan Komering Ulu Timur District. The study was arranged in a Factorial Randomized Block Design, with 9 treatment combinations and 3 replicates. The first factor was the types of fertilizers, consisting of recommended chemical fertilizers (250 kg urea ha-1 + 150 kg SP36 ha-1 + 50 kg KCl ha-1), organic fertilizer from plant residue at 5 Mg ha-1, and lignite-based organic fertilizer (namely Baranik fertilizer) at 0.75 Mg ha-1. The second factor was rice varieties, consisting of Mentik Wangi, Gogo Aromatik and Ciliwung. The application of Baranik fertilizer at 0.75 Mg ha-1 has improved the quality of paddy soil with the increase of organic-C content from 1.44% to 2.90%. Application of Baranik fertilizer at 0.75 Mg ha-1 has increased the vegetative components and the yield of rice about 7.17 Mg ha-1 compared to the organic fertilizer from plant residue, but the yield is still the same as that in the recomended dosages of chemical fertilizers. Among the rice varieties, the yield of Ciliwung variety was higher than other varieties, i.e. 7.62 Mg ha-1. The yield of Gogo Aromatik variety is significantly lower than that of Ciliwung variety. Baranik organic fertilizer can be used to improve soil fertility for food security purpose.